2004
DOI: 10.1111/j.1600-0897.2004.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Colony‐Stimulating Factor Levels in Amniotic Fluid Before and After the Onset of Labor Do Not Differ in Normal Pregnancies

Abstract: M-CSF in amniotic fluid may not contribute to the onset of labor in term pregnancy and/or labor resulting in subsequent delivery may not induce the production and secretion of M-CSF into amniotic cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…38,39 Moreover, in term parturition, Hayashi et al revealed that elevated levels of M-CSF in AF were not associated with the onset of labor in term pregnancy and labor, which result in subsequent delivery. 40 However, to date, there has been a paucity of data regarding the altered levels of M-CSF in the CVF in PPROM pregnancies complicated by MIAC/IAI and SPTB. In the context of preterm labor and premature cervical dilation, our previous studies have shown that elevated CVF levels of M-CSF are independently associated with MIAC in women presenting with preterm labor or SPTB at <32 weeks in cases with premature cervical dilation.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Moreover, in term parturition, Hayashi et al revealed that elevated levels of M-CSF in AF were not associated with the onset of labor in term pregnancy and labor, which result in subsequent delivery. 40 However, to date, there has been a paucity of data regarding the altered levels of M-CSF in the CVF in PPROM pregnancies complicated by MIAC/IAI and SPTB. In the context of preterm labor and premature cervical dilation, our previous studies have shown that elevated CVF levels of M-CSF are independently associated with MIAC in women presenting with preterm labor or SPTB at <32 weeks in cases with premature cervical dilation.…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether M‐CSF levels in amniotic fluid were increased during labor compared with those in women who were not in labor. Consequently, there was not any difference between the two groups, showing that M‐CSF levels in amniotic fluid in laboring group were similar to those in non‐laboring group 20 . This implies that it is possible to compare M‐CSF levels in amniotic fluid in term gravidas including women in labor and those not in labor to M‐CSF levels in controls.…”
Section: Discussionmentioning
confidence: 87%
“…M-CSF and GM-CSF are highly related to the maintenance of pregnancy and the pathophysiology of preeclampsia. However, M-CSF [25] and GM-CSF [26] in amniotic fl uid may not relate to the onset of term labor. In contrast, amniotic fl uid TNF-may contribute to the onset of term labor and / or term labor leading to subsequent delivery may induce the production and secretion of TNF-into the amniotic cavity.…”
Section: Non-labor Groupmentioning
confidence: 88%